2015
DOI: 10.1371/journal.pone.0124772
|View full text |Cite
|
Sign up to set email alerts
|

Association between Inflammation and Cardiac Geometry in Chronic Kidney Disease: Findings from the CRIC Study

Abstract: BackgroundLeft ventricular hypertrophy (LVH) and myocardial contractile dysfunction are independent predictors of mortality in patients with chronic kidney disease (CKD). The association between inflammatory biomarkers and cardiac geometry has not yet been studied in a large cohort of CKD patients with a wide range of kidney function.MethodsPlasma levels of interleukin (IL)-1β, IL-1 receptor antagonist (IL-1RA), IL-6, tumor necrosis factor (TNF)-α, transforming growth factor (TGF)-β, high-sensitivity C-Reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
(44 reference statements)
5
52
2
1
Order By: Relevance
“…Findings from the Chronic Renal Insufficiency Cohort study showed that plasma levels of pro‐inflammatory cytokines and positive acute‐phase proteins were higher in subjects with lower levels of kidney function 12. We showed that specific inflammatory biomarkers are associated with cardiac geometry and risk of atrial fibrillation in patients with CKD 13, 14. Potential causes of inflammation in CKD include chronic subclinical infections, volume overload, increased oxidative stress, sympathetic overactivity, poor nutrition, and vitamin D deficiency, which are also risk factors for CVD.…”
mentioning
confidence: 71%
“…Findings from the Chronic Renal Insufficiency Cohort study showed that plasma levels of pro‐inflammatory cytokines and positive acute‐phase proteins were higher in subjects with lower levels of kidney function 12. We showed that specific inflammatory biomarkers are associated with cardiac geometry and risk of atrial fibrillation in patients with CKD 13, 14. Potential causes of inflammation in CKD include chronic subclinical infections, volume overload, increased oxidative stress, sympathetic overactivity, poor nutrition, and vitamin D deficiency, which are also risk factors for CVD.…”
mentioning
confidence: 71%
“…(2) Long‐term LVH can induce left ventricular dysfunction and decrease blood perfusion in the glomeruli, resulting in renal tubular ischemia. (3) In patients with LVH, the associated inflammatory response, indicated by, for example, elevated plasma levels of high‐sensitivity C‐reactive protein and interleukin‐6, may contribute to and accelerate the progression of systolic dysfunction and cause rapid progression of CKD …”
Section: Discussionmentioning
confidence: 99%
“…LVH emerges as an adaptive response to overload, such as pressure or volume, to some extent, but long‐term LVH leads to left ventricular dysfunction, resulting in the constriction of the renal arteries, less blood‐perfusion of the glomeruli, and alteration of the glomerular membrane filtration coefficient and tubular reabsorption . The inflammatory response associated with LVH also contributes to the progression of CKD . Thus, LVH appears to be a type of adverse cardiac remodeling that contributes to risk factors of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent sympathetic activation can trigger cardiac hypertrophy and fibrosis through activation of the immune system 58 . Accordingly, in patients with stage 3-5 CKD, concentric left ventricular hypertrophy is associated with inflammation 70,71 and with high levels of noradrenaline 72 and neuro peptide Y 73 . High levels of these biomarkers underlie high cardiovascular risk in CKD 74,75 .…”
Section: Box 1 | Circadian Control Of the Immune And Neuroendocrine Smentioning
confidence: 99%